Effectiveness of histological techniques for early identification of scion rootstock incompatibility - Ksia E.; Gouta H.; Aïachi M. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Traditionally almond was cultivated in Tunisia extensively under rainfed conditions with local almond seedlings as rootstock. The new tendency for modernization of almond orchards has implemented the use of some non native cultivars that are compatible with the existing rootstocks. In order to evaluate the behaviour of some local cultivars for high density orchard some trials were established using the cultivars ‘Achaak’ and ‘Porto’ with ‘GF-677’ and ‘Garnem’ as rootstocks. Early observations revealed a plausible incompatibility of the cultivar ‘Achaak’ with ‘Garnem’. In order to contribute to the understanding of this phenomenon and to detect other cases of scion-rootstocks incompatibility histological techniques were used as an early detection practice. Preliminary results for the combination ‘Achaak’/’Garnem’ showed some discontinuity of cells in the intermediate zone between scion and rootstocks in addition to an accumulation of black points of starch. Moreover, observations in field showed low circumferences values and weak growth of both parts. Our work reveals for the first time this scion-rootstock incompatibility and underlines the necessity of biochemical tools for a better understanding of this phenomenon.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)